Electroluminescent fiber as well as preparation method and application thereof

By adopting a combined structure of a conductive fiber body and an electroluminescent layer in the electroluminescent fiber, the problem of poor luminescent stability in the prior art in the stretched state is solved, and the mechanical properties are adjustable and long-term luminescent stability is achieved. suitable for wearable devices.

CN119243386APending Publication Date: 2025-01-03SHANGHAI TECH UNIV

Patent Information

Application Number
CN202310805993.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing electroluminescent fibers have poor luminescence stability in the tensile state and are difficult to meet the mechanical stability and long-term functional stability requirements of wearable devices.

Method used

A combined structure of a conductive fiber body and an electroluminescent layer is adopted, wherein the conductive fiber body is arranged parallel and spaced, the electroluminescent layer is coated on the surface of the conductive fiber body and filled its gap, and the electric field is enhanced by coatings of the dielectric layer and the luminescent layer. Intensity and reduce potential energy loss to ensure luminescence stability under tensile conditions.

Benefits of technology

The mechanical properties of electroluminescent fibers are adjusted, the elongation of break and the strength of break are adjustable within a specific range, maintaining good luminescence stability, low threshold driving voltage, washing and weather resistance, and are suitable for wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243386A_ABST
    Figure CN119243386A_ABST
Patent Text Reader

Abstract

The invention discloses an electroluminescent fiber as well as a preparation method and application thereof. The electroluminescent fiber comprises n conductive fiber bodies and an electroluminescent layer, wherein n is greater than or equal to 2; wherein the conductive fiber bodies are parallel to one another and are arranged at intervals; the electroluminescent layer is coated on the surfaces of the conductive fiber bodies and is filled in gaps among the conductive fiber bodies. The electroluminescent fiber provided by the invention has the advantages of being adjustable in mechanical property and capable of keeping good luminescence stability in a tensile state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to electroluminescent fiber and its preparation method and application. Background Art

[0002] With the development of flexible displays, related fields such as artificial skin, soft machines, and human-machine interfaces have been rapidly promoted, thanks to the inherent mechanical compliance, functional scalability, and adaptability to various scenarios of these devices. Among various flexible display devices, fiber-based display platforms are usually the first choice because flexible displays are mainly used in wearable devices that need to be integrated with a variety of flexible surfaces, such as fabrics and skin. The multi-scale structural designability of fibers allows maximizing or enhancing the flexibility of devices to adapt to various applications.

[0003] At present, the common luminous fiber devices on the market mainly include light-emitting diodes and cold light. Light-emitting diode fibers have advantages such as low voltage drive and high brightness, but they are not flexible and difficult to integrate on wearable fabrics; cold light is a luminous fiber that can produce high brightness and high color temperature light. Its structure includes internal and external electrodes and a light-emitting layer sandwiched in the middle, and is encapsulated in a plastic sleeve on the outermost layer. However, the diameter of cold light is relatively thick and hard to weave, so its application is also limited.

[0004] In addition, the outer transparent electrode of the flexible light-emitting fiber constructed by the existing coaxial spinning technology is usually made of a composite of polymers and conductive nanomaterials (such as silver nanowires, carbon nanotubes and graphene), which makes it difficult to achieve uniform coating over long distances. Moreover, once the tensile strain exceeds a certain value, the connectivity of these nanomaterials will be lower than the percolation threshold, resulting in a sharp drop in conductivity, affecting the luminescence performance of the device, and making it difficult to meet the mechanical stability and long-term functional stability requirements of wearable displays.

[0005] Therefore, how to provide mechanical adjustability of fibers and maintain long-term luminescence stability under stretching conditions is a technical problem that urgently needs to be solved in this field. Summary of the invention

[0006] The present invention provides an electroluminescent fiber and its preparation method and application to overcome the defects of the electroluminescent fiber in the prior art that the mechanical properties of the electroluminescent fiber are limited in scope and it is difficult to maintain good luminescence stability in a stretched state. The electroluminescent fiber provided by the present invention has the advantages of adjustable mechanical properties and good luminescence stability in a stretched state.

[0007] The present invention provides an electroluminescent fiber, which comprises n conductive fiber bodies and an electroluminescent layer, where n≥2;

[0008] Wherein, the conductive fibers are parallel to each other and arranged at intervals;

[0009] The electroluminescent layer is coated on the surface of the conductive fiber body and filled in the gaps between the conductive fiber bodies.

[0010] In the present invention, the conductive fiber body may include a conductive fiber core, and the surface of the conductive fiber core is independently coated or not coated with a coating; the coating is a dielectric layer or a luminescent layer. The coating can prevent short circuits between the conductive fiber bodies and can enhance the electric field strength of the luminescent layer, thereby reducing the loss of electric potential energy.

[0011] The thickness of the coating is preferably 10 μm-100 μm, such as 20 μm, 50 μm or 60 μm.

[0012] In some embodiments, n=2, and surfaces of the conductive fiber cores in the two conductive fiber bodies are both coated with a dielectric layer.

[0013] In some embodiments, n=2, and surfaces of the conductive fiber cores in the two conductive fiber bodies are both coated with a light-emitting layer.

[0014] In some specific embodiments, the surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a dielectric layer, and the dielectric layer includes dielectric nanoparticles and an elastic polymer.

[0015] Wherein, the dielectric nanoparticles are preferably strontium titanate and / or barium titanate.

[0016] The elastic polymer preferably includes one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; and the solid content of the water-based polyurethane is preferably 30%-50%.

[0017] The mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (0.3-2):1, more preferably (0.3-0.8):1 or (0.5-2):1, for example 3:2.

[0018] When the dielectric nanoparticles are strontium titanate and the elastic polymer is waterborne polyurethane, the mass ratio of the strontium titanate to the waterborne polyurethane is (0.5-2):1, for example, 3:2.

[0019] When the dielectric nanoparticles are barium titanate and the elastic polymer is polydimethylsiloxane, the mass ratio of the barium titanate to the polydimethylsiloxane is (0.3-0.8):1.

[0020] In some specific embodiments, the surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a luminescent layer, and the luminescent layer includes luminescent particles and an elastic polymer.

[0021] The luminescent particles are preferably ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles.

[0022] The elastic polymer preferably includes one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; and the solid content of the water-based polyurethane is preferably 30%-50%.

[0023] The mass ratio of the luminescent particles to the elastic polymer is preferably (5-50):10, such as 5:2 or 1:1.

[0024] Wherein, the light-emitting layer preferably further includes dielectric nanoparticles; the dielectric nanoparticles are preferably strontium titanate and / or barium titanate; the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-10):10, for example 1:4.

[0025] In the present invention, the conductive fiber core in the conductive fiber body may be selected from metal fibers and / or conductive composite fibers.

[0026] Wherein, the conductive composite fiber preferably includes a fiber matrix and a conductive coating; the fiber matrix is ​​preferably one or more of polyamide fiber, polyester fiber, rubber fiber and silk protein fiber; the conductive coating is preferably one or more of silver nanowires, carbon nanofibers and an adhesive containing metal particles.

[0027] In some embodiments, the conductive fiber core may be a metal fiber, which may produce a rigid electroluminescent fiber.

[0028] In some embodiments, the conductive fiber core may be a polyamide fiber, which may produce a semi-flexible electroluminescent fiber.

[0029] In some embodiments, the conductive fiber core may be rubber fiber and / or silk protein fiber, and an electroluminescent fiber with flexibility and good stretchability can be produced.

[0030] In the present invention, the electroluminescent layer may include luminescent particles and elastic polymers.

[0031] The luminescent particles are preferably ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles.

[0032] The elastic polymer preferably includes one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; the solid content of the water-based polyurethane is preferably 30%-50%, for example 35%.

[0033] The mass ratio of the luminescent particles to the elastic polymer is preferably (5-50):10, such as 5:2 or 1:1.

[0034] Wherein, the light-emitting layer preferably further includes dielectric nanoparticles; the dielectric nanoparticles are preferably strontium titanate and / or barium titanate; the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-10):10, for example 1:4.

[0035] In some embodiments, the diameter of the conductive fibers may be independently 50 μm to 200 μm; and the resistance of the conductive fibers may be independently 10 Ω / cm to 50 Ω / cm.

[0036] In some embodiments, the diameter of the conductive fibers may be independently 0.5 mm to 2 mm; and the resistance of the conductive fibers may be independently 0.1 Ω / cm to 10 Ω / cm.

[0037] In some embodiments, the diameter of the conductive fiber bodies may be independently 0.2 mm to 1 mm; and the resistance of the conductive fiber bodies may be independently 20 kΩ / cm to 500 kΩ / cm.

[0038] In the present invention, the diameter of the electroluminescent fiber may be 200 μm-2000 μm.

[0039] In the present invention, the length of the electroluminescent fiber may be ≥20 m.

[0040] The present invention also provides a method for preparing the electroluminescent fiber as described above, which comprises the following steps: arranging n conductive fiber bodies in parallel and at intervals, and simultaneously coating them with an electroluminescent layer solution to form an electroluminescent layer, thereby obtaining the electroluminescent fiber; wherein n≥2; and the electroluminescent layer is coated on the surface of the conductive fiber body and filled in the gaps between the conductive fiber bodies.

[0041] In the present invention, the operation of synchronous coating may be to continuously coat and collect n conductive fiber bodies passing through a dip coating tank containing an electroluminescent layer solution at a preset rate in parallel, and then heat to obtain the electroluminescent fibers. During the synchronous coating process, the capillary force (Fc) between two parallel conductive fiber bodies is beneficial to the diffusion of the liquid formed by the luminescent layer solution along the long axis direction. Secondly, a Laplace force (FL) is generated in the cross-section where the liquid forms the electroluminescent layer. Thirdly, a Laplace pressure difference (FD) is generated in the direction of the curvature radius of the wave itself, which can weaken the instability. On the double parallel conductive fiber bodies, the curvature radius of the wave crest is smaller than that of the wave trough (Rp < Rt), resulting in FL-p > FL-t, so as to promote the formation of a uniform fluid coating on the double parallel fibers. If the coating is uneven, it will affect the mechanical properties of the conductive fiber bodies. The coating method of the present invention can obtain a uniform electroluminescent layer and overcome the influence of reduced mechanical properties caused by uneven coating.

[0042] Among them, the preset rate is preferably 5 - 50 mm / s, for example, 12 mm / s.

[0043] Among them, the heating temperature is preferably 60°C - 180°C, for example, 100°C.

[0044] Among them, the heating time is preferably 10 s - 60 s, for example, 10 s.

[0045] Among them, the number of coating times is preferably 1 - 3 times, for example, 1 time.

[0046] In some specific embodiments, the surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a luminescent layer or a dielectric layer, and its preparation method may be: passing the conductive fiber core through a dip coating tank containing a luminescent layer solution or a dielectric layer solution at a preset rate through a guiding device for continuous coating; then heating and drying to form the dielectric layer or the luminescent layer.

[0047] Among them, the preset rate is preferably 5 - 50 mm / s, for example, 12 mm / s.

[0048] Among them, the heating temperature is preferably 60°C - 180°C, for example, 100°C or 110°C.

[0049] Among them, the heating time is preferably 10 s - 60 s, for example, 10 s.

[0050] Among them, the number of coating times is preferably 2 - 10 times, more preferably 4 - 10 times, for example, 2 times or 4 times.

[0051] The method for preparing the dielectric layer solution is preferably as follows: dispersing the dielectric nanoparticles in the elastic polymer and then performing ultrasonic treatment. The ultrasonic treatment time is preferably 10-30 minutes.

[0052] In some embodiments, the dielectric layer solution further comprises n-hexane.

[0053] When the dielectric nanoparticles are barium titanate and the elastic polymer is polydimethylsiloxane, the dielectric layer solution also includes n-hexane, and the mass ratio of the barium titanate to the polydimethylsiloxane is (0.3-0.8):1; the mass ratio of the polydimethylsiloxane to the n-hexane is (1-10):1.

[0054] When the elastic polymer is silicone rubber, the dielectric layer solution further comprises n-hexane, and the mass ratio of the silicone rubber to the n-hexane is (1-10):1.

[0055] The method for preparing the luminescent layer solution is preferably as follows: dispersing the luminescent particles in the elastic polymer under stirring; the stirring time is preferably 10-30 min; the stirring rate is preferably 100-400 r / min, for example 300 r / min.

[0056] The present invention also provides the use of the electroluminescent fiber as described above in a light-emitting device.

[0057] The present invention also provides a light-emitting device, which comprises the fabric formed by the electroluminescent fibers as described above.

[0058] In the present invention, the light emitting device further comprises: a sensor and a processor electrically connected to the electroluminescent fiber; wherein the electroluminescent fibers are electrically connected to the processor respectively and form a preset pattern; and the sensor is preferably a light sensor or a sound sensor.

[0059] In the present invention, the fabric can be a fabric that uses an automatic embroidery machine or other method to weave the electroluminescent fiber into various designs for light-emitting display, and is controlled by a driver chip with multi-channel control capability; after receiving real-time data from a data transmission unit, the fabric for light-emitting display transmits the signal to a microcontroller unit, which processes the corresponding signal and drives the display fabric to dynamically display numbers and patterns. The pattern can be set as needed, such as a seven-segment digital display pattern or a 5×5 array pattern.

[0060] The present invention also provides a voice interactive luminous display, which includes the light-emitting device as described above.

[0061] In the present invention, the voice interactive luminous display application can be used to identify including but not limited to human voice categories, environmental noise, human sentences, realize real-time semantic dialogue display, and provide audio-visual assistance for hearing-impaired patients, and can be used to issue alarm prompts to provide safety protection.

[0062] In the present invention, the voice interactive luminous display can adopt a convolutional neural network (CNN) model and a Mel spectrum map recognition method to identify the human voice category, the type and frequency of environmental noise, and can be combined with the recognition of human sentences to achieve a more comprehensive voice recognition application.

[0063] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0064] The reagents and raw materials used in the present invention are commercially available.

[0065] The positive and progressive effects of the present invention are:

[0066] (1) The mechanical properties of the electroluminescent fiber designed in the present invention can be widely adjusted, and the elongation at break of the electroluminescent fiber can be adjusted within the range of 20%-450%, and the breaking strength can be adjusted within the range of 0.2MPa-100MPa, which can meet the mechanical property requirements of various flexible displays.

[0067] In some embodiments, the elongation at break of the electroluminescent fiber is 20%-40%, and its breaking strength is 70MPa-75MPa; in other embodiments, the elongation at break of the electroluminescent fiber is 80%-90%, and its breaking strength is 71MPa; in other embodiments, the elongation at break of the electroluminescent fiber is 300%-400%, and its breaking strength is 0.2MPa-0.5MPa.

[0068] (2) The electroluminescent fiber provided by the present invention can maintain good luminescence stability in a stretched state. In some preferred embodiments, when the stretched length is 200%, the luminescence intensity can be kept equivalent to that in the initial state.

[0069] (3) The electroluminescent fiber provided by the present invention also has a low threshold driving voltage (threshold driving voltage is defined as the brightness of the light-emitting device reaching 1 cd m -2 The voltage when the friction is applied can be as low as 21V, and the luminescence can be driven by the voltage generated by the frictional electric fabric without the need for additional energy supply; it also has good washability and can still maintain good luminescence performance after washing; and it can withstand changes in environmental temperature and humidity, and maintain a stable luminescence state under high temperature and low humidity or low temperature and high humidity.

[0070] (4) The electroluminescent fiber provided by the present invention can be used as a luminous fabric to be bonded or woven into wearable products, such as clothes, flexible fabrics, etc.; and can be further applied to voice interactive luminous displays. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Reference numerals:

[0072] The first conductive fiber body 1, the second conductive fiber body 2, the first light-emitting layer 11, the second light-emitting layer 21, the electroluminescent layer 3, the first light-emitting layer 11a, the second light-emitting layer 21a, the feeding roller 51, the first guide roller 52, the immersion roller 53, the second guide roller 54, the collecting roller 55, and the dipping tank 56.

[0073] Figure 1 It is a schematic diagram of the preparation process of the electroluminescent fiber in the present invention.

[0074] Figure 2 It is a schematic diagram of the principle of the first conductive fiber body and the second conductive fiber body being arranged in parallel and stably and continuously coated in the present invention.

[0075] Figure 3 Schematic cross-sectional view of the electroluminescent fiber in Examples 1, 4 and 5.

[0076] Figure 4 Schematic cross-sectional view of the electroluminescent fiber in Examples 2 and 3.

[0077] Figure 5 This is the SEM image of the electroluminescent fiber in Example 3-5.

[0078] Figure 6 This is a diagram showing the mechanical properties of the electroluminescent fibers prepared in Examples 3-5.

[0079] Figure 7 Schematic diagram of the weight bearing of the electroluminescent fiber prepared in Example 3.

[0080] Figure 8 This is a diagram showing the elastic properties of the electroluminescent fiber prepared in Example 5.

[0081] Fig. 9 This is a diagram showing the luminous intensity effect of the electroluminescent fiber prepared in Example 2 during 10,000 stretching-bending cycle tests.

[0082] Fig.10 A schematic diagram is provided for Example 5 showing that the electroluminescent fiber maintains stable luminescence during the process of being stretched to 400% and maintains stable luminescence during the process of being stretched to 200% for 50 cycles.

[0083] Fig.11This is a schematic diagram of the relationship between the threshold driving voltage and luminous intensity of the electroluminescent fiber provided in Example 3.

[0084] Fig.12 Schematic diagram of the pattern and fabric woven by the electroluminescent fibers provided in Examples 3-5.

[0085] Fig.13 This is a diagram showing the luminous state of the fabric woven from the electroluminescent fibers provided in Example 2 before and after washing.

[0086] Fig.14 This is a schematic diagram of the luminous state of the electroluminescent fiber woven fabric provided in Example 2 under high temperature and low humidity or low temperature and high humidity.

[0087] Fig.15 Schematic diagram of the electroluminescent fiber woven fabric provided in Example 3 driven to emit light by friction electrostatic means.

[0088] Fig.16 A schematic diagram of the state of a fabric woven from electroluminescent fibers used for audio-visual interactive intelligent display is provided for Example 3. DETAILED DESCRIPTION

[0089] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0090] Sources of conductive polyamide fiber (conductive nylon fiber) and conductive polyester fiber: silver nylon filament from Qingdao Zhiyuan Xiangyu Functional Fabric Co., Ltd.;

[0091] Specifications and parameters of conductive polyamide fiber (conductive nylon fiber): fineness 40D; resistance 15Ω / cm; 40D / 12F; ingredients: polyamide fiber impregnated with silver ions;

[0092] Specifications and parameters of conductive polyester fiber (conductive polyester fiber): fineness 100D; resistance 15Ω / cm; 100D / 36F; ingredients: polyester fiber impregnated with silver ions;

[0093] The conductive polyamide fiber and the conductive polyester fiber can be made in a homemade way or purchased in a commercial way.

[0094] In the present invention, the coated guide device can be as follows Figure 1As shown in the figure, it is composed of a feeding roller 51, a first guide roller 52, an immersion roller 53 for immersing the conductive polyamide fiber in the electroluminescent layer solution, a second guide roller 54, a collecting roller 55, and a dipping tank 56. Among them, a hollow heating tube (not shown in the figure) is arranged between the second guide roller 54 and the collecting roller 55; the conductive fiber core or the conductive fiber body passes through the feeding roller 51, the first guide roller 52, the collecting roller 55, the second guide roller 54, and the collecting roller 55 in sequence.

[0095] Example 1

[0096] (1) at room temperature of 20-25° C., dispersing ZnS:Cu luminescent particles in aqueous polyurethane having a solid content of 35% and magnetically stirring for 15 minutes to obtain a luminescent layer solution, wherein the mass ratio of the luminescent particles to the aqueous polyurethane is 5:2, and the stirring rate of the magnetic stirrer is 300 rpm;

[0097] (2) Conductive polyamide fiber (conductive nylon fiber) is selected as the conductive fiber core, the conductive fiber core is wound on a guide device, and is continuously pre-coated and collected through a dip coating tank containing a luminescent layer solution at a rate of 12 mm / s, and heated in a hollow heating tube at 100° C. for 10 seconds to obtain a conductive fiber body coated with a luminescent layer. This pre-coating process is repeated 4 times, and the coating thickness on the surface of the conductive fiber body is about 50 μm;

[0098] (3) Two sections are cut from the conductive fiber body obtained in step (2), which are respectively used as the first conductive fiber body 1 having the first luminescent layer 11 and the second conductive fiber body 2 having the second luminescent layer 21, and are passed through a dipping tank containing an electroluminescent layer solution in parallel, and are continuously coated and collected at a rate of 12 mm / s, and heated in a hollow heating tube at 100°C for 10 seconds to obtain an electroluminescent fiber having an electroluminescent layer 3; this dipping process is repeated once, and the obtained electroluminescent fiber has a diameter of about 400 μm and a length of more than 20 m. The first conductive fiber body 1 and the second conductive fiber body 2 are arranged in parallel and spaced apart to form a parallel dual-fiber electrode structure; the electroluminescent layer 3 is coated on the first luminescent layer 11 and the second luminescent layer 21, and the principle schematic diagram of the synchronous coating is shown in the figure. Figure 2 shown.

[0099] In addition, it is worth mentioning that the conductive fiber body in this embodiment can also be cut into two sections before pre-coating to respectively constitute a first conductive fiber core and a second conductive fiber core, and then pre-coated with a luminescent layer solution to form a first conductive fiber body 1 having a first luminescent layer 11 and a second conductive fiber body 2 having a second luminescent layer 21, and then perform step (3).

[0100] Example 2

[0101] (1) at room temperature of 20 to 25° C., dispersing barium titanate nanoparticles in aqueous polyurethane having a solid content of 35%, ultrasonically treating for 15 minutes, and then magnetically stirring for 15 minutes to obtain a dielectric layer solution, wherein the mass ratio of the barium titanate nanoparticles to the aqueous polyurethane is 3:2, and the stirring rate of the magnetic stirrer is 300 rpm;

[0102] (2) Conductive polyamide fiber (conductive nylon fiber) is selected as the conductive fiber core, the conductive fiber core is wound on a guide device, and is continuously pre-coated and collected through a dipping tank containing the dielectric layer solution prepared in step (1) at a rate of 12 mm / s, and heated in a hollow heating tube at 100° C. for 10 seconds to obtain a conductive fiber body coated with a dielectric layer. This pre-preg coating process is repeated twice, and the coating thickness on the surface of the conductive fiber body is about 20 μm.

[0103] (3) At room temperature of 20-25° C., the ZnS:Cu luminescent particles were dispersed in an aqueous polyurethane having a solid content of 35%, and magnetically stirred for 15 minutes, wherein the mass ratio of the luminescent particles to the aqueous polyurethane was 5:2, and the stirring rate was 300 rpm.

[0104] (4) Two sections are cut from the conductive fiber body obtained in step (2) to serve as the first conductive fiber body 1 having the first dielectric layer 11a and the second conductive fiber body 2 having the second dielectric layer 21a, respectively. The two sections are passed through a dipping tank containing an electroluminescent layer solution in parallel, and are continuously coated and collected at a rate of 12 mm / s. After heating in a hollow heating tube at 100°C for 10 seconds, an electroluminescent fiber having an electroluminescent layer 3 is obtained. The dipping process is repeated once, and the obtained electroluminescent fiber has a diameter of about 250 μm and a length of more than 20 m. The first conductive fiber body 1 and the second conductive fiber body 2 are arranged in parallel and spaced apart to form a parallel dual-fiber electrode structure. The electroluminescent layer 3 covers the first dielectric layer 11a and the second dielectric layer 21a.

[0105] (5) Use the convolutional neural network algorithm to train the human voice recognition model to achieve human voice recognition. The model is installed on the control end (PC or mobile phone APP), and a human-computer interaction interface is built. The control end and the above-mentioned electroluminescent fiber are connected through a driver chip. When human voice appears in the surrounding, the human-computer interaction interface and the 5*5 display array woven by the luminous fiber read the prediction results at the same time, providing real-time prediction (such as Fig.16 shown).

[0106] In addition, it is worth mentioning that the conductive fiber body coated with the dielectric layer in this embodiment can also be cut into two sections before pre-coating to respectively constitute a first conductive fiber core and a second conductive fiber core, and then pre-coated with a dielectric layer solution to form a first conductive fiber body 1 having a first dielectric layer 11a and a second conductive fiber body 2 having a second dielectric layer 21a.

[0107] Example 3

[0108] (1) At room temperature of 20-25° C., barium titanate nanoparticles are dispersed in aqueous polyurethane having a solid content of 35%, subjected to ultrasonic treatment for 15 minutes, and then magnetically stirred for 15 minutes to obtain a dielectric layer solution, wherein the mass ratio of the barium titanate nanoparticles to the aqueous polyurethane is 3:2, and the stirring rate of the magnetic stirrer is 300 rpm.

[0109] (2) Conductive polyamide fiber (conductive nylon fiber) is selected as the conductive fiber core, the conductive fiber core is wound on a guide device, and is continuously pre-coated and collected through a dipping tank containing the dielectric layer solution prepared in step (1) at a rate of 12 mm / s, and is heated in a hollow heating tube at 100° C. for 10 seconds to obtain a conductive fiber body coated with a dielectric layer; this pre-impregnation coating process is repeated twice, and the coating thickness on the surface of the conductive fiber body is about 20 μm.

[0110] (3) At room temperature of 20-25° C., ZnS:Cu luminescent particles and barium titanate nanoparticles were dispersed in an aqueous polyurethane having a solid content of 35%, and magnetically stirred for 15 minutes to obtain an electroluminescent layer solution, wherein the mass ratio of the luminescent particles to the barium titanate nanoparticles and the aqueous polyurethane was 10:1:4, and the stirring rate of the magnetic stirrer was 300 rpm.

[0111] (4) Two sections are cut from the conductive fiber body obtained in step (2) to serve as the first conductive fiber body 1 having the first dielectric layer 11a and the second conductive fiber body 2 having the second dielectric layer 21a, respectively, and are passed through a dip coating tank containing an electroluminescent layer solution in parallel, and are continuously coated and collected at a rate of 12 mm / s, and heated in a hollow heating tube at 100°C for 10 seconds to obtain an electroluminescent fiber having an electroluminescent layer 3. This dip coating process is repeated once, and the obtained electroluminescent fiber has a diameter of about 250 μm and a length of more than 20 m. The first conductive fiber body 1 and the second conductive fiber body 2 are arranged in parallel and spaced apart to form a parallel dual-fiber electrode structure. The electroluminescent layer 3 covers the first dielectric layer 11a and the second dielectric layer 21a.

[0112] (5) The electroluminescent fiber is woven into a 5×5 array pattern using an automatic embroidery machine or other method, and is controlled by a driver chip with multi-channel control capability.

[0113] (6) Use the "sphinx" speech recognition engine to recognize the content of the speech, and realize real-time communication of human-computer interaction through a preset dialogue model. The above-mentioned speech content recognition and dialogue model are installed on the control end (PC end or mobile phone APP), and a human-computer interaction interface is built. The control end and the above-mentioned electroluminescent fiber are connected through a driver chip. When human voices appear around, the speech recognition engine recognizes the speech content and gives a corresponding answer according to the dialogue model. The answer result is read simultaneously on the human-computer interaction interface and the 5*5 display array woven by the luminous fiber, providing real-time prediction (such as Fig.16 (as shown in Part B of FIG.

[0114] In addition, it is worth mentioning that the conductive fiber body coated with the dielectric layer in this embodiment can also be cut into two sections before pre-coating to respectively constitute a first conductive fiber core and a second conductive fiber core, and then pre-coated with a dielectric layer solution to form a first conductive fiber body 1 having a first dielectric layer 11a and a second conductive fiber body 2 having a second dielectric layer 21a.

[0115] Example 4

[0116] (1) At room temperature of 20-25° C., ZnS:Cu luminescent particles were dispersed in aqueous polyurethane with a solid content of 35%, and then magnetically stirred for 15 minutes to obtain a luminescent layer solution, wherein the mass ratio of the luminescent particle dispersion to the aqueous polyurethane was 5:2, and the stirring rate of the magnetic stirrer was 300 rpm.

[0117] (2) Conductive polyester fiber (conductive polyester fiber) is selected as the conductive fiber core, the conductive fiber core is wound on a guide device, and is continuously pre-coated and collected at a rate of 12 mm / s through a dipping tank containing the luminescent layer solution prepared in step (1), and is heated in a hollow heating tube at 110° C. for 10 seconds to obtain an electroluminescent fiber. This pre-coating process is repeated 4 times, and the coating thickness on the surface of the conductive fiber core is about 60 μm.

[0118] (3) Two sections are cut from the conductive fiber body obtained in step (2) to serve as the first conductive fiber body 1 having the first luminescent layer 11 and the second conductive fiber body 2 having the second luminescent layer 21, respectively, and are passed through a dip coating tank containing an electroluminescent layer solution in parallel, and are continuously coated and collected at a rate of 12 mm / s, and are heated in a hollow heating tube at 100° C. for 10 seconds to obtain an electroluminescent fiber having an electroluminescent layer 3. This dip coating process is repeated once, and the obtained electroluminescent fiber has a diameter of about 550 μm and a length of more than 20 m. The first conductive fiber body 1 and the second conductive fiber body 2 are arranged in parallel and spaced apart to form a parallel dual-fiber electrode structure, and the electroluminescent layer 3 covers the first luminescent layer 11 and the second luminescent layer 21.

[0119] In addition, it is worth mentioning that the conductive fiber body coated with the luminescent layer in this embodiment can also be cut into two sections before pre-coating to respectively constitute a first conductive fiber core and a second conductive fiber core, and then pre-coated with a luminescent layer solution to form a first conductive fiber body 1 having a first luminescent layer 11 and a second conductive fiber body 2 having a second luminescent layer 21.

[0120] Example 5

[0121] (1) The silkworm cocoons were degummed by boiling them in a 0.5% (w / w) NaHCO3 solution for 30 minutes, and the degumming process was repeated twice. The degummed silk was then washed with distilled water and dried in an oven at 60°C for 12 hours. Then, 4 g of lithium chloride was dissolved in 100 g of formic acid, and then 10 g of the degummed silk was added. The mixture was vigorously stirred at room temperature of 20 to 25°C for 1 hour. After filtering through gauze to remove impurities, the resulting solution was poured into a silicone rubber mold and placed under 65% RH for 3 days to produce a silk protein ion conductor.

[0122] (2) A piece of silk protein ion conductor is prepared into conductive silk protein fiber through the steps of cutting, stretching, twisting and self-healing, and then ZnS:Cu luminescent particles are dispersed in a silicone rubber solvent (dispersant) consisting of ecoflex00-30 silicone rubber and n-hexane at room temperature of 20-25°C, and a luminescent layer solution is obtained after magnetic stirring for 15 minutes, wherein the mass ratio of the luminescent particles, silicone rubber and n-hexane is 1:1:0.5, and the stirring rate is 300 rpm.

[0123] (3) The conductive silk protein fiber is used as the conductive fiber core, and is passed through a dipping tank containing the light-emitting layer solution prepared in step (2) for continuous pre-coating of the surface layer, and is heated in an oven at 60°C for 10 minutes. This pre-coating process is performed once, and the coating thickness on the surface of the conductive fiber body is about 50 μm.

[0124] (4) Two conductive fibers are cut from the conductive fiber body obtained in step (3) to serve as the first conductive fiber body 1 having the first luminescent layer 11 and the second conductive fiber body 2 having the second luminescent layer 21, respectively, and are passed through a dip coating tank containing an electroluminescent layer solution in parallel, and are continuously coated and collected at a rate of 12 mm / s, and heated in an oven at 60° C. for 10 minutes to obtain an electroluminescent fiber having an electroluminescent layer 3. This dip coating process is performed once, and the obtained electroluminescent fiber has a diameter of about 1.5 μm and a length of more than 20 cm. The first conductive fiber body 1 and the second conductive fiber body 2 are arranged in parallel and spaced apart to form a parallel dual-fiber electrode structure. The luminescent layer 3 covers the first luminescent layer 11 and the second luminescent layer 21.

[0125] Obviously, it should be noted that in addition to the manual or other methods described above, the pre-coating and parallel coating processes of the first conductive fiber body 1 and the second conductive fiber body 2 in this embodiment can also be processed using the guide device provided in any of the above embodiments.

[0126] In addition, it is worth mentioning that the conductive fiber body coated with the luminescent layer in this embodiment can also be cut into two sections before pre-coating to respectively constitute a first conductive fiber core and a second conductive fiber core, and then pre-coated with a luminescent layer solution to form a first conductive fiber body 1 having a first luminescent layer 11 and a second conductive fiber body 2 having a second luminescent layer 21.

[0127] Application Examples

[0128] A light-emitting device comprises a fabric formed by weaving the electroluminescent fibers prepared in any one of the above embodiments.

[0129] Take human voice recognition as an example

[0130] 1) Collect a large number of voices of the elderly, children, adult men, and adult women, and build a recognition model based on the convolutional neural network algorithm to achieve real-time recognition of human voices;

[0131] 2) Connect the model to the PC and use the tkinter library to build a human-computer interaction interface;

[0132] 3) The PC segment and the luminous fiber are connected through a single-chip microcomputer. When there is human voice around, the model receives and recognizes the sound, and transmits the sound recognition result to the luminous fiber. The human-computer interaction interface and the luminous fiber display the recognition result at the same time. For example, if there is a female voice speaking around, the human-computer interaction interface displays "female" and the luminous ion skin displays "F" (female), realizing real-time sound prediction.

[0133] Effect Example

[0134] Mechanical properties test method: The mechanical test was performed using a tensile testing machine (Instron 5966, Instron, Norwood, USA) with a tensile rate of 50 mm / min. The two ends of the sample were fixed to the two end clamps of the testing machine, the frame height was adjusted so that the sample was at the zero load point, and the initial length, width and thickness of the sample were measured.

[0135] Sample size: Length: 20mm

[0136] Mechanical properties testing equipment: tensile testing machine (Instron 5966, Instron, Norwood, USA);

[0137] Luminous performance testing equipment: Spectrocolorimeter (PR655).

[0138] Table 1

[0139]

[0140]

[0141] Table 2

[0142] Stretched length <![CDATA[Luminous intensity (cd m -2 )]]> 0% 12 100% 10 200% 10 300% 8 400% 4

[0143] Table 3

[0144] Cycle times <![CDATA[Luminous intensity (cd m -2 )]]> 0 times 12 10 times 12 20 times 11 30 times 11 40 times 11 50 times 10

[0145] According to the data in Table 1, it can be seen that according to the application scenario, the present invention can provide an electroluminescent fiber with a breaking elongation between 20% and 450%, a Young's modulus between 0.1 and 202 MPa, a toughness not less than 0.5 MJm-3, a breaking strength range of 0.2-75 MPa, and a luminous intensity of 78 cd m in the initial state. -2 -238cd m -2 , the threshold driving voltage is 21V-315V, according to Table 2, Table 3 and Fig.10 It can be seen from the data in that the electroluminescent fiber of the present invention maintains good luminescence stability during the stretching process.

[0146] Examples 1, 4 and 5 are schematic cross-sectional views of electroluminescent fibers obtained by pre-coating a luminescent layer and then simultaneously coating an electroluminescent layer. Figure 3 As shown; Examples 2 and 3 are schematic cross-sectional views of electroluminescent fibers obtained by pre-coating a node layer and then simultaneously coating an electroluminescent layer. Figure 4 shown.

[0147] Figure 5 The SEM image of the electroluminescent fiber prepared in Example 3-5 shows the internal structure of the electroluminescent fiber of the present invention. The luminescent layer is coated on the surface of the conductive fiber body and fills the gap between the conductive fiber body.

[0148] Figure 6 The figure shows the mechanical properties effect diagram of the electroluminescent fiber prepared in Examples 3-5, wherein the blue icon is the breaking strength of Examples 3-5 under different strains, and the yellow icon is the stiffness of Examples 3-5 under different strains. In the stress-strain diagram, the black curve represents the data of Example 3; the blue curve represents the data of Example 4; and the brown curve represents the data of Example 5; Figure 7The weight-bearing schematic diagram of the electroluminescent fiber of Example 3 is shown. Combined with the data in Table 1, it can be seen that different types of conductive fiber cores have different mechanical properties, and different conductive fiber cores can be selected in combination with other necessary technical features of the present invention to achieve mechanical adjustability for different application scenarios.

[0149] Figure 8 The effect diagram of the elastic properties of the electroluminescent fiber prepared in Example 5 is shown, and it can be seen that the electroluminescent fiber prepared in the present invention has good elastic properties and can recover quickly after being stretched.

[0150] Fig. 9 This is a graph showing the luminous intensity of the electroluminescent fiber prepared in Example 2 during 10,000 stretching-bending cycle tests. It can be seen that the luminous intensity of the electroluminescent fiber remains at a stable level after 10,000 stretching-bending cycles.

[0151] Fig.11 The figure shows the relationship between the driving voltage and the luminous intensity of the electroluminescent fiber provided in Example 3. It can be seen that when the driving voltage is 412.5V, the luminous intensity can reach 238cd m -2 .

[0152] Fig.12 Shown are schematic diagrams of patterns woven by the electroluminescent fibers provided in Examples 3-5 and fabrics. It can be seen that the electroluminescent fibers provided by the present invention can be woven into desired patterns and integrated on fabrics.

[0153] Fig.13 The luminous state display diagram of the fabric woven with electroluminescent fibers provided in Example 2 before and after washing is shown. Three one-hour standard washing tests were carried out using an automatic washing machine and laundry detergent. By comparison, it can be seen that the electroluminescent layer of the electroluminescent fiber is not damaged after multiple washings and maintains stable luminescence.

[0154] Fig.14 A schematic diagram of the luminous state of the electroluminescent fiber woven fabric provided in Example 2 under high temperature and low humidity or low temperature and high humidity is shown, which will not affect its use even in extreme or harsh environments.

[0155] Fig.15 Schematic diagram of the electroluminescent fiber woven fabric provided in Example 3 driven to emit light by tribostatic means. It can be seen that it has a low threshold driving voltage, and can be driven to emit light by the voltage generated by the triboelectric fabric without the need for additional energy supply.

[0156] Fig.16 A schematic diagram of the state of a fabric woven from electroluminescent fibers used for audio-visual interactive intelligent display is provided for Example 3.

[0157] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0158] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. An electroluminescent fiber, characterized in that: It includes n conductive fiber bodies and an electroluminescent layer, n≥2; Wherein, the conductive fibers are parallel to each other and arranged at intervals; The electroluminescent layer is coated on the surface of the conductive fiber body and filled in the gaps between the conductive fiber bodies.

2. The electroluminescent fiber according to claim 1, characterized in that: The conductive fiber body comprises a conductive fiber core, and the surface of the conductive fiber core is independently coated or not coated with a coating; the coating is a dielectric layer or a luminescent layer; the thickness of the coating is preferably 10 μm-100 μm, such as 20 μm, 50 μm or 60 μm; Preferably, n=2, and the surfaces of the conductive fiber cores in the two conductive fiber bodies are both coated with a dielectric layer; Preferably, n=2, and surfaces of the conductive fiber cores in the two conductive fiber bodies are both coated with a light-emitting layer.

3. The electroluminescent fiber according to claim 2, characterized in that: The surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a dielectric layer, and the dielectric layer includes dielectric nanoparticles and an elastic polymer; wherein the dielectric nanoparticles are preferably strontium titanate and / or barium titanate; the elastic polymer is preferably one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; the solid content of the water-based polyurethane is preferably 30%-50%; the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (0.3-2):1, more preferably (0.3-0.8):1 or (0.5-2):1, for example 3:2; And / or, the surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a luminescent layer, and the luminescent layer includes luminescent particles and an elastic polymer; wherein the luminescent particles are preferably ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles; the elastic polymer preferably includes one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; the solid content of the water-based polyurethane is preferably 30%-50%, for example 35%; the mass ratio of the luminescent particles to the elastic polymer is preferably (5-50):10, for example 5:2 or 1:1; the luminescent layer preferably also includes dielectric nanoparticles; the dielectric nanoparticles are preferably strontium titanate and / or barium titanate; the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-10):10, for example 1:4; And / or, the conductive fiber core is selected from metal fibers and / or conductive composite fibers; the conductive composite fibers preferably include a fiber matrix and a conductive coating; the fiber matrix is ​​preferably one or more of polyamide fibers, polyester fibers, rubber fibers and silk protein fibers; the conductive coating is preferably one or more of silver nanowires, carbon nanofibers and an adhesive containing metal particles.

4. The electroluminescent fiber according to claim 1, characterized in that: The electroluminescent layer comprises luminescent particles and an elastic polymer; wherein the mass ratio of the luminescent particles to the elastic polymer is preferably (5-50):10, for example, 5:2; the luminescent particles are preferably ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles; the elastic polymer preferably comprises one or more of polyurethane, polydimethylsiloxane and silicone rubber; the polyurethane is preferably water-based polyurethane; the solid content of the water-based polyurethane is preferably 30%-50%, for example, 35%; The electroluminescent layer preferably further comprises dielectric nanoparticles, and the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-10):10, for example 1:4; the dielectric nanoparticles are preferably strontium titanate and / or barium titanate.

5. The electroluminescent fiber according to claim 1, characterized in that: The conductive fiber body satisfies any one of the following conditions ac: a. The diameter of the conductive fiber body is independently 50μm-200μm; the resistance of the conductive fiber body is independently 10Ω / cm-50Ω / cm; b. The diameter of the conductive fiber body is independently 0.5mm-2mm; the resistance of the conductive fiber body is independently 0.1Ω / cm-10Ω / cm; c. The diameter of the conductive fiber body is independently 0.2mm-1mm; the resistance of the conductive fiber body is independently 20kΩ / cm-500kΩ / cm; And / or, the diameter of the electroluminescent fiber is 200 μm-2000 μm; the length of the electroluminescent fiber is ≥20 m.

6. A method for preparing an electroluminescent fiber as claimed in any one of claims 1 to 5, characterized in that: It includes the following steps: The electroluminescent fiber is obtained by arranging n conductive fibers in parallel and at intervals, and coating an electroluminescent layer solution simultaneously to form an electroluminescent layer; wherein n≥2; and the electroluminescent layer is coated on the surface of the conductive fibers and fills the gaps between the conductive fibers.

7. The method for preparing the electroluminescent fiber according to claim 6, characterized in that: The synchronous coating operation is to pass n conductive fiber bodies through a dipping tank containing an electroluminescent layer solution in parallel at a preset rate for continuous coating and collection, and then heat to obtain the electroluminescent fiber; Among them, the preset rate is preferably 5-50mm / s, such as 12mm / s; the heating temperature is preferably 60℃-180℃, such as 100℃; the heating time is preferably 10s-60s, such as 10s; the number of coatings is preferably 1-3 times, such as 1 time.

8. The method for preparing the electroluminescent fiber according to claim 6, characterized in that: The surface of the conductive fiber core in at least one of the conductive fiber bodies is coated with a dielectric layer or a luminescent layer. The preparation method of the dielectric layer or the luminescent layer is: the conductive fiber core is passed through a dipping tank containing a luminescent layer solution or a dielectric layer solution at a preset rate through a guide device for continuous coating; then heated and dried to form the dielectric layer or the luminescent layer; Wherein, the preset rate is preferably 5-50 mm / s, such as 12 mm / s; the heating temperature is preferably 60°C-180°C, such as 100°C or 110°C; the heating time is preferably 10s-60s, such as 10s; the number of coatings is preferably 2-10 times, more preferably 4-10 times, such as 4 times; The method for preparing the dielectric layer solution is preferably as follows: dispersing the dielectric nanoparticles in the elastic polymer, and then performing ultrasonic treatment, wherein the ultrasonic treatment time is preferably 10-30 minutes; The method for preparing the luminescent layer solution is preferably as follows: dispersing the luminescent particles in the elastic polymer under stirring; the stirring time is preferably 10-30 min; the stirring rate is preferably 100-400 r / min, for example 300 r / min.

9. Use of the electroluminescent fiber according to any one of claims 1 to 5 in a light-emitting device.

10. A light emitting device, characterized in that: The fabric comprises the electroluminescent fiber according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Luminous color changing fabric and preparation method thereof

    CN108505187A

  • Luminescent fiber and preparation method thereof

    CN113745426A

  • Electroluminescent fiber and preparation method thereof

    CN114892286A

  • Electroluminescent fiber, yarn and fabric and preparation method thereof

    CN116288766A

  • Ac electroluminescent power cord and device comprising same

    US20200323052A1

Cited By

  • Preparation method of electroluminescent fiber and auxiliary communication electroluminescent device prepared from electroluminescent fiber

    CN120273052A